The Right to Education for Ethnic Minority Women and Girls in Vietnam - Nguyen Thi Hong Yen; Do Qui Hoang (University of Jember, 2022)
The right to education is a fundamental human right that has been widely recognized by the United Nations and in core international human rights instruments. Over the years as an active and responsible member of the international community, Vietnam has always worked on amending its laws to fulfill international commitments that would create an equal legal environment for the enjoyment of fundamental rights, including the right to access education. However, given their unique characteristics, ethnic minority women and girls still face discrimination and dual inequalities in their living environment, including those arising from both their ethnicity and gender. Difficulties in accessing education have led to a low percentage of ethnic minority women working in professional and technical jobs; most do simple jobs with low incomes. Barriers to education or employment generally arise due to gender stereotypes and male chauvinism. With this in mind, this article will focus on the following matters to address and resolve issues related to the right to education for ethnic minority women and girls in Vietnam: (i) an analysis of the international legal framework and Vietnam’s law on topics of gender equality in education for ethnic minority women and girls; (ii) a discussion on the reality of adopting rights to education for ethnic minority women and girls in Vietnam; (iii) identification of barriers and challenges that ethnic minority women and girls face when pursuing their educational rights; and (iv) recommendations for Vietnam to ensure the right to education for ethnic minority women and girls in the future. Keywords: Human rights, minority’s rights, the right to education, gender equality, women’s rights.